Implementasi Metode SAS (Struktural Analitik Sintetik) untuk Meninggkatkan Kemampuan Membaca Permulaan Siswa Kelas I SD Negeri 44 Halmahera Selatan - Rachmatia Tauhid (Jurnal Ilmiah Wahana Pendidikan, 2022)
Synthetic Structural Analytical SAS method in improving early reading in the first grade of elementary school. This study aims to improve the initial reading ability of first graders of SD Negeri 44 Halmahera Selatan. This study uses the class action method which is carried out in two cycles, each cycle includes a planning stage , implementation, observation, and reflection. The results include: the use of the SAS method can work well and improve the students' initial reading ability in grade I SD Negeri 44 Halmahera Selatan, the background of the problem in this study is the low reading skills of students who do not reach the KKM (Minimum Completeness Criteria) set by schools, namely 70 with 12 students who did not reach KKM 8 students (40%) and completed 4 students 52% based on the problem, the research conducted CAR using this method can be seen from the results of observing activities in cycle I with a presentation of 60% meeting I category enough , 70% of the second meeting was very good at improving in the second cycle from the data above it can be concluded that the reading of grade 1 students at SD Negeri 44 South Halmahera. The main purpose of pre-reading is to get a start. Beginning of reading is a reading activity that seeks to understand the contents of the reading/text as a whole. A person is said to understand reading well if he has the ability. Reading is an activity or cognitive process that seeks to find various information contained in writing, this means that early reading is a thought process to understand the contents of the beginning of the text being read, therefore reading is not just looking at a collection in the form of words, syllable sentences, letters, but more than that reading is an activity of understanding and interpreting symbols, signs, meaningful writing so that the message conveyed by the author can be accepted by the reader.